Mirai [videorecording (DVD)] - Hosoda, Mamoru, 1967-; Hosoda, Mamoru, 1967-; Sinterniklaas, Michael; Sinterniklaas, Michael (Universal Pictures Home Entertainment, 2019)
Four-year-old Kun is jealous of his new baby sister until one day when he storms off into the garden and meets her as a teenager from the future.